Elastic properties of rocks from the seismogenic zone and minimum fault size to nucleate megathrust earthquakes - Hanaya Okuda; Yuya Akamatsu; Manami Kitamura; Michiyo Sawai (Progress in Earth and Planetary Science)
Abstract The elastic properties of rocks in subduction zones are indicators of the stress states and determine the critical length required for earthquake nucleation. We measured the elastic properties of core samples collected from the Susaki area in the Shimanto accretionary complex in southwestern (SW) Japan, which was exhumed from the seismogenic zone depths. We found that the samples have P-wave velocities of 5.1–5.4 (dry) and 5.4–5.8 km/s (wet), S-wave velocities of 3.2–3.3 (dry) and 3.0–3.3 km/s (wet), and porosities of 1.0–2.5%. According to microstructural observations, tight contact among grains owing to the pressure solution and cementation processes may lead to low porosity and high velocity. We examined relationships between velocity and porosity using rock physics models and found the potential of the model to describe the elastic properties of rocks from shallow to deep depths toward the seismogenic zone. The obtained elastic properties were used to estimate the critical nucleation length for a megathrust earthquake along a plate boundary fault. The estimated critical nucleation length for a megathrust earthquake is less than a few meters, even when the pore fluid pressure is higher than the hydrostatic pressure. This length can be a key parameter for examining the factors controlling nucleation processes in the seismogenic zone.